2021
DOI: 10.1042/cs20201060
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of endocannabinoid concentrations in human subcutaneous adipose tissue in obesity and modulation by omega-3 polyunsaturated fatty acids

Abstract: Obesity is believed to be associated with a dysregulated endocannabinoid system which may reflect enhanced inflammation. However, reports of this in human white adipose tissue (WAT) are limited and inconclusive. Marine long-chain omega-3 polyunsaturated fatty acids (LC n-3 PUFAs) have anti-inflammatory actions and therefore may improve obesity-associated adipose tissue inflammation. Therefore, fatty acid (FA) concentrations, endocannabinoid concentrations, and gene expression were assessed in subcutaneous WAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…10,12 We previously reported altered endocannabinoid concentrations in subcutaneous WAT (scWAT) in individuals with obesity in comparison to normal weight individuals. 13 Oxylipins elicit a range of both pro-and anti-inflammatory actions. Pro-inflammatory actions of oxylipins synthesised from the omega-6 PUFA arachidonic acid (AA) include promoting infiltration and activation of immune cells, 14À16 altering lipid metabolism, 17 and promoting WAT expansion and remodelling.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…10,12 We previously reported altered endocannabinoid concentrations in subcutaneous WAT (scWAT) in individuals with obesity in comparison to normal weight individuals. 13 Oxylipins elicit a range of both pro-and anti-inflammatory actions. Pro-inflammatory actions of oxylipins synthesised from the omega-6 PUFA arachidonic acid (AA) include promoting infiltration and activation of immune cells, 14À16 altering lipid metabolism, 17 and promoting WAT expansion and remodelling.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…21À24 We previously reported EPA and DHA to increase the concentrations of two endocannabinoids, eicosapentaenoyl ethanolamide and docosahexaenoyl ethanolamide, in scWAT in normal weight individuals but that this effect of LC n-3 PUFAs is impaired in individuals with obesity. 13 It has been suggested that deficiency of SPMs in obesity may contribute to dampened immunity and poor response to viral infections 25 but reports of altered concentrations of SPMs in WAT in human obesity are limited, as highlighted by Pal et al 25,26 and Han et al 27 In addition to potentially influencing oxylipin formation, EPA and DHA elicit their actions via altering the activity of transcription factors to modulate inflammation and other processes in WAT. 28,29 Furthermore, EPA and DHA can bind to receptors such as peroxisome proliferator activated receptors (PPARs) 30 to regulate the expression of genes associated with lipid accumulation in WAT, 31,32 and to G-protein coupled receptor (GPR)-120 to regulate inflammation and insulin sensitivity.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…This issue is relevant in human studies aimed at evaluating tissue modulation of NAE biosynthesis by dietary FA using circulating levels of NAE as biomarkers. Interestingly, our data showed that changes of AEA and DHEA in the VAT significantly correlated with those in the plasma, suggesting that their systemic levels may reflect changes in the adipose tissue [55]. Interestingly, DHEA plasma levels were also correlated to those in liver and brain, while circulating SEA and PEA may significantly reflect their changes only in the liver.…”
Section: Discussionmentioning
confidence: 50%
“…Linoleic acid and α-linolenic acid are the essential precursors of omega-6 and omega-3 families, respectively. Therefore, changing the percentage of dietary FA, such as linoleic acid, participates to modulate the bioavailability of eCB levels [ 161 , 162 , 163 , 164 ].…”
Section: The Ecbs Are Modulated In Obesitymentioning
confidence: 99%